The Impact of Remittance Inflows on Economic Growth in ASEAN Countries: A Panel Data Analysis - Jamaluddin; St. Hatidja; Azizurrohman, Muhammad (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
This study investigates at how remittance inflows affect economic growth in ASEAN nations, with a particular emphasis on GDP per capita between 2000 and 2023. The study examines the connections between remittances and GDP per capita using panel data regression analysis, taking financial development, inflation, and unemployment into account. According to the fixed effects model, GDP per capita rises by 0.128% for every 1% increase in remittances as a percentage of GDP. The findings also show that inflation and unemployment have a negative impact, whereas financial progress has a beneficial one. The robustness of the model is shown by the R-squared value of 0.45. This study highlights the value of financial development and macroeconomic stability while offering empirical support for the role that remittances play in promoting economicprogress.The findings offer policy insights for optimizing remittance benefits to achieve sustainable development in ASEAN countries